Scoping Study on Ethiopian Sesame Value Chain - Kassie, Girma T.; Worku, Yonas; Bachewe, Fantu Nisrane; Asnake, Woinishet; Abate, Gashaw T. (International Food Policy Research Institute, 2022)
The Consultative Group for International Agricultural Research (CGIAR) is the largest non-profit public agricultural research group globally. Recently, it has restructured itself into One-CGIAR with the intention of integrating its capabilities, knowledge, assets, people, and global presence for a new era of intercon nected and partnership-driven research towards achieving the Sustainable Development Goals (SDGs). One-CGIAR led the development of about 30 initiatives that aimed at addressing one more of the key impact areas of SDGs. One of these initiatives is “Rethinking Food Markets and Value Chains for Inclu sion and Sustainability,” referred to as rethinking markets in short. Rethinking Markets Initiative aims to provide evidence on what types of bundled innovations, incentive structures, and policies are most effec tive for creating more equitable sharing of income and employment opportunities in growing food markets, while reducing the food sector’s environmental footprint. The initiative has four work packages addressing different but interrelated issues and that are being implemented in one or more countries. Work Package 1 (WP1) is about making globally integrated value chains inclusive, efficient, and environmentally sustainable.